38. ATTITUDES TOWARD FERTILITY AND CHILDBEARING AMONG FEMALE STUDENTS AT UNIVERSITY OF MEDICINE AND PHARMACY ACCORDING TO THE AFCS SCALE (Vietnam Journal of Community Medicine, 2025)
Objective: Assessment of attitudes toward fertility and future childbearing needs among female students of the University of Medicine and Pharmacy - Vietnam National University (UMP-VNU), Hanoi by using the AFCS.Subjects and methods: A cross-sectional study on 187 female students at the University of Medicine and Pharmacy – Vietnam National University, Hanoi.Results: 66.3% expressed a desire for future childbearing, while 33.7% were uncertain. Significant differences were found between age groups (≤22 years: 60% vs. >22 years: 85.1%) and relationship status (single: 62.2% vs. in a relationship: 79.5%). Mean scores for “Importance of fertility for the future,” “Childbearing as a hindrance at present” and “Female identity” were 3.41 ± 0.97, 3.90 ± 0.74, and 2.96 ± 0.93, respectively. Older students (>22 years), those from rural areas, those with cohabiting parents, and those desiring children placed greater importance on fertility (p < 0.05). Regardless of group, all participants acknowledged the challenges of childbearing at present. Higher agreement with childbearing as part of cultural identity was observed among older students, rural residents, lower-income groups, those with cohabiting parents, and those desiring children (p < 0.05).Conclusion: 66.3% expressed a desire for future childbearing, a lower rate than in previous studies, influenced by age and marital status. Most participants recognized the importance of childbearing but also perceived it as a burden in the present. More positive attitudes toward childbearing were observed in older students, rural residents, lower-income groups, and those with cohabiting parents.
Keywords: Childbearing; AFCS; UMP-VNU